Training and Capacity Development of SI-MFS Actors in Bangladesh - Ahmed, S.; Miajy, Abdullah; Debnath, Manik; Haque, Abudul; Bhandari, Humnath (International Rice Research Institute, 2023)
The objectives of the training were as follows: - To improve the productivity and profitability of crops, vegetables, fruits, cattle, and poultry. - Enhance farmers’ food and nutrition security through diversified crops and livestock production. - To aware village people about the nutritional importance of vegetables and motivate them to properly use homestead areas for year-round vegetable production. - To train them on modern and climate-smart production technologies. ➢ To train them on biofertilizer (compost and vermicompost) and bio-pesticide preparation and use. - To develop local service providers (LSP) to ensure sustainable availability of quality seeds and seedlings to the local farmers. - To create employment opportunities for women and youth.